2019
DOI: 10.1021/acscatal.9b02245
|View full text |Cite
|
Sign up to set email alerts
|

Strategies toward Selective Electrochemical Ammonia Synthesis

Abstract: The active and selective electroreduction of atmospheric nitrogen (N2) to ammonia (NH3) using energy from solar or wind sources at the point of use would enable a sustainable alternative to the Haber–Bosch process for fertilizer production. While the process is thermodynamically possible, experimental attempts thus far have required large overpotentials and have produced primarily hydrogen (H2). In this Perspective, we show how insights from electronic structure calculations of the energetics of the process, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
159
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 178 publications
(160 citation statements)
references
References 64 publications
0
159
0
1
Order By: Relevance
“…Recently, we proposed models that demonstrated how the large availability of protons in aqueous systems is the main reason why selectivity to NRR is so low . Following this model, we herein focus on non‐aqueous electrolytes, where the activity of protons can be controlled independently of catalyst surface by operating at a low proton concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we proposed models that demonstrated how the large availability of protons in aqueous systems is the main reason why selectivity to NRR is so low . Following this model, we herein focus on non‐aqueous electrolytes, where the activity of protons can be controlled independently of catalyst surface by operating at a low proton concentration.…”
Section: Introductionmentioning
confidence: 99%
“…We further calculated the kinetic barrier of adsorbed N 2 reduction to *N−*NH to assess the kinetic activity of Mo Mn +Vo@α‐MnO 2 (001) used as electrocatalyst of NRR. It is found that the formation of *N−*NH needs to overcome a low kinetic barrier of 0.8 eV comparable with that intrinsic barrier for the electrochemical steps (0.7 eV), meaning the fast kinetics for cathode reaction (Figure S8).…”
Section: Resultsmentioning
confidence: 96%
“…116,117 Current strategies include the use of three-dimensional materials and bio-inspired materials, as well as the use of non-aqueous electrolytes. 92,118,119…”
Section: Sustainable Ammonia Synthesismentioning
confidence: 99%